The mathematical understandings acquired by high school seniors - Reyes, Perla (Abad) 1919- ([Quezon City University of the Philippines], 1953)
This study determined if high school seniors are able to think and act in terms of mathematical ideas and principles, if the students have acquired functional competence in the following aspects of mathematics: understanding, problem solving, basic computations, and judgment, and if there are any necessary shifts of emphasis to be made in the mathematics curriculum in high school.
Bibliography: p. 72-76.
Thesis (M.Ed.)--University of the Philippines, 1953
Typewritten
Vita
Keywords: Mathematics -- Study and teaching